2013
DOI: 10.1136/vr.101366
|View full text |Cite
|
Sign up to set email alerts
|

Farm animal practitioners' views on their use and expectations of veterinary diagnostic laboratories

Abstract: Diagnostic sampling of farm animals by private veterinary practitioners can be an important contributing factor towards the discovery of emerging and exotic diseases. This focus group study of farm animal practitioners in Northern Ireland investigated their use and expectations of diagnostic veterinary laboratories, and elicited their opinions on the role of the private practitioner in veterinary surveillance and the protection of rural public health. The veterinarians were enthusiastic users of diagnostic lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Chalmers believed that the staff shortages would continue as vets were in short supply, and were unlikely to be attracted into the Department given restrictions on government expenditure. To gain perspective on this shortage of vets, Connolly [41] reported that there were 130 vets in private large animal practice in 1966, compared to around 300 in 2013 [42], with an increase in the total cattle population of just 25% in the intervening period: the numbers of cattle to be tested per vet would indeed have been challenging. Earlier reports in mid-1975 had lamented that there were 25 vacancies in private practice which could not be filled, and that the Department had also been operating significantly under-capacity, at least 25 vets short of a full complement [43].…”
Section: Matters Of Concernmentioning
confidence: 99%
“…Chalmers believed that the staff shortages would continue as vets were in short supply, and were unlikely to be attracted into the Department given restrictions on government expenditure. To gain perspective on this shortage of vets, Connolly [41] reported that there were 130 vets in private large animal practice in 1966, compared to around 300 in 2013 [42], with an increase in the total cattle population of just 25% in the intervening period: the numbers of cattle to be tested per vet would indeed have been challenging. Earlier reports in mid-1975 had lamented that there were 25 vacancies in private practice which could not be filled, and that the Department had also been operating significantly under-capacity, at least 25 vets short of a full complement [43].…”
Section: Matters Of Concernmentioning
confidence: 99%
“…The group discussion setting enabled the comparison of the different opinions that are exchanged between participants during sessions (Morgan 1993, Kitzinger and Barbour 1999, Bryman 2012). These methods are emerging as useful tools in assessing behaviours in veterinary medicine (Coe and others 2007, Gunn and others 2008, Kaler and Green 2013, Robinson and Epperson 2013, Sheehan 2013). …”
Section: Introductionmentioning
confidence: 99%
“…An integrated approach to collecting and using qualitative data to investigate health problems in veterinary medicine is increasingly being recognized [ 37 , 38 , 39 ]. Even with smaller sample sizes compared to quantitative research, the findings of qualitative research are often indicative of the beliefs and experiences of the wider population from which the sample is drawn [ 40 ].…”
Section: Methodsmentioning
confidence: 99%